Pengaruh Green Marketing Terhadap Brand Image KFC Naughty by Nature Senopati Jakarta Selatan - Desvia Dwiana Putri Ayuningtias; Ratih Hasanah Sudradjat (Jurnal Ilmiah Wahana Pendidikan, 2022)
In this era, the issue of global warming is a main problem that felt by entire population of the earth. With the increasing number of campaigns to save the earth, the industrial sector also switched to using environmentally friendly marketing strategies. Namely KFC which issued KFC Naughty by Nature with its trademark production of healthy food menus with quality ingredients. This study was conducted to determine how much influence green marketing has on KFC Naughty by Nature Senopati, South Jakarta brand image. The research was conducted using quantitative methods through a testing process, namely regression analysis, coefficient of determination, hypothesis, validity, and reliability. The results of hypothesis testing, it shows that green marketing influences KFC Naughty by Nature Senopati, South Jakarta brand image. The calculation results get the results that the value of t count is greater than t table because t count is 20.306 and t table is 1.960. So, Ha is accepted, which means that there is an influence between green marketing on KFC Naughty by Nature Senopati, South Jakarta brand image. And from the results of the coefficient of determination, green marketing has an effect of 50.9% on the KFC Naughty by Nature Senopati, South Jakarta brand image.